An unusual source of septic pulmonary embolism: Perianal abscess in an immunocompetent patient - Ved Prakash; Ajay Kumar Verma; Ankit Bhatia; Virendra Kumar; Surya Kant; Karthik Nagaraju (Archives of Medicine and Health Sciences, 2015)
Septic pulmonary embolism (SPE) is a rare clinical presentation mostly seen in patients who are immunocompromised, in which septic thrombi from an infectious nidus are transported in the vascular system of the lungs. We report a patient presenting with features of sepsis and respiratory distress; chest X-ray and computed tomography (CT) thorax of whom showed multiple bilateral small thick-walled cavities associated with right pleural effusion. He was found to have a septic source of Enterococcus sp. cultured from a perianal abscess with the same bacteremia. Pulmonary septic embolism from the abscess was diagnosed by radiology and correlation of bacteremia from septic foci and blood culture. The clinical condition improved with surgical management of the perianal abscess and appropriate antibiotic treatment.